PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN UMKM DI KOTA BANDUNG DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Rezky Afiahtul Barokah; Ginanjar Wira Saputra (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Based on the Resource-Based View (RBV) and leadership theories, this study aims to analyze the influence of leadership style and organizational communication on employee performance in Micro, Small, and Medium Enterprises (MSMEs) in Bandung City, with work motivation as a mediating variable. The novelty of this research lies in revealing the anomaly of work motivation's role and the dominance of task-oriented leadership in the MSME sector. This explanatory quantitative research involved 96 MSME employee respondents selected through a purposive sampling technique. Data analysis utilized Partial Least Square - Structural Equation Modeling (PLS-SEM), a method methodologically justified as highly robust for testing complex predictive models on limited sample sizes. The test results prove that leadership style and organizational communication have a positive and significant effect on work motivation. Leadership style is also proven to have a significant direct effect on performance. However, organizational communication and work motivation have no significant impact on performance, thus motivation fails as a mediating variable. Interpretatively, this motivation failure indicates that employees' internal drive is vulnerable to being hindered by the absence of standard operational work systems or limited facilities in MSMEs, so it does not manifest in actual performance. Practically, this research concludes that MSME performance improvement cannot merely rely on internal motivational drives. MSME actors are recommended to invest in task-oriented leadership and the provision of technical operational instruments such as Standard Operating Procedures (SOP) to ensure target achievement.